Monitoring, information technology and the labor share - Dorothee Schneider (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2011)
This paper assesses empirically the hypotheses by Bental and Demougin (2010) that innovations in ICT (Information and Communication Technology) reduce the labor share in OECD countries by improving the monitoring technology. In a first step, I show that data trends for the labor share, wages in effciency units, and labor in effciency units over capital can be matched by a simulation of the model of Bental and Demougin (2010). In a second approach, I confirm increasing monitoring of workers using micro data for Germany. I argue that ICT in uences labor not only through substitutability of labor with ICT and foreign work, but also through to lowering rents of workers as monitoring technology improves.
Keywords: D24; J30; E25; 330; labor shares; bargaining; monitoring; Lohnquote; Informationstechnik; Personalkontrolle; Lohnverhandlungstheorie; Verhandlungsmacht; Schätzung; OECD-Staaten